1997
DOI: 10.1021/ic960870a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of H−H versus Si−H σ-Bond Coordination and Activation on 16e Metal Fragments. Organosilane, N2, and Ethylene Addition to the Agostic Complex W(CO)3(PR3)2and Dynamic NMR Behavior of the Latter

Abstract: Variable-temperature (31)P{(1)H} NMR spectroscopy of the agostic complexes M(CO)(3)(PCy(3))(2) (M = Mo, W) indicates dynamic behavior as evidenced by collapse below -20 degrees C of a singlet to an AB signal plus a shifted singlet. The inequivalency of the phosphines is possibly due to the presence of conformational isomers resulting from hindered rotation of the M-P bond or, less likely, a geometric isomer with pseudo-cis PCy(3) ligands. Further studies on the coordination chemistry of W(CO)(3)(PR(3))(2) (R =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 126 publications
2
62
1
Order By: Relevance
“…The 29 Si satellites on the latter hydride signal provided the 1 J Si-H value of 93 Hz, which is in a similar range as has recently been observed for similar g 2 -silane compounds ( 1 J Si-H = 98 Hz for [W(CO) 5 (g 2 -H-SiHPh 2 )]) [11], proving the correct assignment of this signal to the g 2 -H-SiHEt 2 moiety of the g 2 -silane complex. The 183 W satellites on the hydride signal allowed us to calculate the 1 J W-H = 38 Hz, which is very close to those observed for other a-agostic hydrides [10,11,20,21,38]. Based on these data, the signal can be assigned without a doubt to the intermediate compound [W(CO) 5 (g 2 -H-SiHEt 2 )] (A) (Scheme 1).…”
Section: Spectroscopic Characterization Of Intermediate Compoundssupporting
confidence: 71%
See 2 more Smart Citations
“…The 29 Si satellites on the latter hydride signal provided the 1 J Si-H value of 93 Hz, which is in a similar range as has recently been observed for similar g 2 -silane compounds ( 1 J Si-H = 98 Hz for [W(CO) 5 (g 2 -H-SiHPh 2 )]) [11], proving the correct assignment of this signal to the g 2 -H-SiHEt 2 moiety of the g 2 -silane complex. The 183 W satellites on the hydride signal allowed us to calculate the 1 J W-H = 38 Hz, which is very close to those observed for other a-agostic hydrides [10,11,20,21,38]. Based on these data, the signal can be assigned without a doubt to the intermediate compound [W(CO) 5 (g 2 -H-SiHEt 2 )] (A) (Scheme 1).…”
Section: Spectroscopic Characterization Of Intermediate Compoundssupporting
confidence: 71%
“…Two sets of 29 Si satellites of the W-H resonance result from the presence of two silicon ligands at the tungsten centre. The 1 J Si-H value of 43 Hz is a typical J Si-H value for g 2 -silane complexes, which usually falls in the range 30-100 Hz [1,[16][17][18][19][20][21][32][33][34], and proves a r (Si-H) interaction with the tungsten centre. The second J Si-H value of 34 Hz establishes the presence of another silicon atom at the tungsten center, coupled with a proton through two bonds.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In 1997, Butts et al [12] reported the synthesis and structure of W(CO) 3 (PCy 3 ) 2 (g 2 -C 2 H 4 ) which agrees with structure 1. An interesting structural feature in this complex is the coplanar orientation of the ethylene and phosphine ligands.…”
Section: Introductionmentioning
confidence: 74%
“…Associated with this is the desire to get more insight into the mechanism of Si-H bond activation by transition metal compounds [20][21][22][23][24][25][26][27][28][29] which in turn is relevant even for the topic of C-H bond activation [30] as well as for the understanding of transition metal-catalyzed oligo-and polysilane formation [31].…”
Section: Introductionmentioning
confidence: 99%